Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - Garcia-Martin, G. (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo

Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - GARCÍA-MARTÍN, G (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo